1993
DOI: 10.1001/archpsyc.1993.01820240013001
|View full text |Cite
|
Sign up to set email alerts
|

Light Therapy in Seasonal Affective Disorder Is Independent of Time of Day or Circadian Phase

Abstract: Both morning and evening light therapy improved depressive symptoms in patients with SAD independent of their circadian phase or sleep timing. These findings argue against a circadian phase-delay hypothesis of the pathophysiology of SAD, or the necessity of a phase-advance by morning light for clinical efficacy. They additionally suggest more practicable and flexible schedules for light therapy in SAD, since time of day is not crucial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
3
2

Year Published

1994
1994
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(66 citation statements)
references
References 36 publications
1
60
3
2
Order By: Relevance
“…There was no correlation of clinical improvement with initial depth of depression in our studies [ 18], where patients' depressions were of medium severity. There was no difference in response rate between patients on con stant antidepressant treatment or without (with the exception of lithium) [18 and unpubl.…”
Section: Swiss Light Therapy Studiescontrasting
confidence: 73%
“…There was no correlation of clinical improvement with initial depth of depression in our studies [ 18], where patients' depressions were of medium severity. There was no difference in response rate between patients on con stant antidepressant treatment or without (with the exception of lithium) [18 and unpubl.…”
Section: Swiss Light Therapy Studiescontrasting
confidence: 73%
“…Concerning the timing of bright light administration, behavioral improvements have been obtained in demented patients with morning as well as evening exposure, and a recent study showed equal effectiveness of morning and evening exposure in seasonal affective disorder as well (Wirz-Justice et al 1993). As far as we know, the present study is the first to apply a whole-day increase in light intensity in patients with disturbed circadian rhythms.…”
Section: Discussionmentioning
confidence: 65%
“…Although some authors have concluded that the timing of light therapy is not crucial (Wirz-Justice et al, 1993;Meesters et al, 1995), most studies show a slight superiority of morning light over evening light (e.g. Lewy et al, 1998;Terman et al, 2001).…”
Section: Discussionmentioning
confidence: 99%